A Hydrophobic Metal–Organic Framework Based on Cubane‐Type [Co4(μ3‐F)3(μ3‐SO4)]3+ Clusters for Gas Storage and Adsorption Selectivity of Benzene over Cyclohexane. Issue 32 (4th July 2016) - Zhang, Lei; Yang, Wenbin; Wu, Xiao‐Yuan; Lu, Can‐Zhong; Chen, Wen‐Zhe
Abstract: Hydrophobic metal‐organic frameworks (MOFs) not only have high water stability, but also exhibit high adsorption capacity towards organic molecules, in particular hydrocarbons. Herein we report a rare metal fluoride organic frameworkMFOF‐1 with high hydrophobicity, which is constructed from unprecedented fluoride‐ and sulfate‐bridged cubane‐type tetranuclear cobalt clusters.MFOF‐1 consists of three types of polyhedral cages with face‐sharing configurations, and possesses a novel (3, 9)‐connected 3D+3D→3D self‐interpenetrating array or the rarepyr topology.MFOF‐1 shows high thermal stability and high stability in water and even acid/base aqueous solutions, and exhibits rather high H2 and CO2 storage capacities at ambient pressure. Remarkably, MFOF‐1 shows little adsorption of water but considerably high uptakes of methanol, n ‐hexane, cyclohexane, and benzene, and exhibits a certain degree of adsorption selectivity of benzene over cyclohexane. Abstract : Hydrophobic pore surface : A hydrophobic metal‐fluoride‐organic framework built up from unprecedented fluoride‐ and sulfate‐bridged cubane‐type tetranuclear cobalt clusters shows high stability in water and even acid/base aqueous solutions. Noteworthy, it exhibits high H2 and CO2 uptakes and considerably high adsorption capacities towards organic molecules but little adsorption of water, together with adsorption selectivity of benzene over cyclohexane (see figure).